High-performance Pt / C catalyst and preparation method thereof
By treating the carbon support with urea and performing hydrothermal treatment, the problem of complex and unenvironmental protection in the prior art was solved, and Pt/C catalyst with high electrochemical activity and stability was prepared, achieving simplified process and performance improvement.
Patent Information
- Application Number
- CN202411527861.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-10-30
AI Technical Summary
In the prior art, the carrier C treatment process of the Pt/C catalyst is complex and not environmentally friendly, has high energy consumption, and the subsequent preparation process of the Pt/C catalyst is cumbersome, making it difficult to amplify production.
Urea is treated with carbon support through equal amounts of impregnation, reducing the number of micropores and increasing the surface nitrogen content. Then, hydrothermal treatment is performed with a mixture of platinum salt precursor, water and glycol to prepare high-performance Pt/C catalyst.
The prepared Pt/C catalyst has a small Pt nanoparticle particle size distribution between 1-10 nm, a high electrochemically active specific surface area, good stability and high peak power density, and is suitable for industrial applications.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention belongs to the field of fuel cells, and in particular relates to a high-performance Pt / C catalyst and a preparation method thereof. Background Art
[0002] Clean energy represented by lithium batteries has become a goal that the whole society generally pursues. Fuel cell technology has advantages over lithium batteries such as high energy density and high power density. It also plays an important role in today's energy transformation. Among them, proton exchange membrane fuel cells are the most widely used. In proton exchange membrane fuel cells, the slow oxygen reduction process at the cathode limits its wide application. Pt / C catalysts are widely used in proton exchange membrane fuel cells due to their good catalytic activity and stability. The carrier has an important influence on its catalytic performance. The preparation of highly active Pt / C catalysts by simply and efficiently modifying the carrier is of great significance to the development of proton exchange membrane fuel cells.
[0003] CN 116779881A discloses a preparation method for preparing a fuel cell catalyst by carrier modification technology, wherein a carbon carrier and an oxidant solution are mixed to obtain a modified carbon carrier, the modified carbon carrier is then mixed with a nitride, and a pretreated carbon carrier is obtained by secondary modification, and the pretreated carbon carrier is then mixed with ethylene glycol to obtain a carbon slurry, and a polyol solution of chloroplatinic acid and an alkaline solution are mixed and then subjected to microwave treatment to obtain a Pt nanocolloid, and the Pt nanocolloid is mixed with the carbon slurry, and the pH is adjusted to obtain a Pt / C catalyst. However, the preparation method has a long process, and an oxidant is required in the carbon carrier modification process, which is not environmentally friendly.
[0004] CN 114171749A discloses a method for preparing a fuel cell catalyst by carrier modification technology, which preliminarily hydrothermally treats a C carrier under high temperature acidic conditions to obtain a highly compatible C, and then prepares a Pt / C catalyst by mixing and reducing it with a precursor solution. This method requires the use of nitric acid, which is seriously polluting to the environment, when treating the carrier, which is not environmentally friendly, and the high temperature process also consumes a lot of energy.
[0005] In the above prior art, the treatment process of the carrier C of the Pt / C catalyst is complicated and not environmentally friendly, with high energy consumption, and the subsequent preparation process of the Pt / C catalyst is cumbersome and difficult to scale up. Therefore, it is necessary to find a simple modification technology of the C carrier for the preparation of high-performance Pt / C catalyst. Summary of the invention
[0006] The purpose of the present invention is to provide a new and simple carrier modification technology to prepare high-performance Pt / C catalysts in view of the defects of the prior art.
[0007] In order to achieve the above object, the present invention adopts the following technical scheme: a high-performance Pt / C catalyst, comprising: a carbon carrier and Pt nanoparticles loaded on the carbon carrier, wherein the carbon carrier is treated with urea by an equal amount of impregnation method before loading.
[0008] Furthermore, the particle size of the Pt nanoparticles is 1-10 nm, and the Pt loading is 10%-60% by mass.
[0009] Furthermore, after the carbon support is treated by the equal amount impregnation method, its surface micropore volume is 0.01~0.05cm 3 / g, micropore specific surface area is 10~65m 2 / g, and the average pore size is 4~8nm.
[0010] Furthermore, after the carbon carrier is treated by the equal amount impregnation method, the surface nitrogen content is 0.5%~25%, and the oxygen content is 5%~15%.
[0011] Furthermore, the carbon carrier is XC-72C, Ketjen black, EC300J, Denka black carbon black or Black Pears2000 carbon black.
[0012] A method for preparing the above-mentioned high-performance Pt / C catalyst comprises the following steps: (1) Pretreatment of the carbon carrier: urea is dispersed in water to form a urea solution, and then the solution is mixed evenly with the carbon carrier, and left at room temperature for 12 to 120 hours, and then placed in an oven at 60 to 120°C for 24 to 48 hours, dried and ground to obtain a pretreated carbon carrier; (2) Preparation of supported catalyst by reduction: The carbon support pretreated in step (1) is added to an ethylene glycol solution to form a support ethylene glycol mixed solution, and an aqueous solution of a platinum salt precursor is added to set the Pt loading to 10 wt% to 60 wt%. The mixture is sealed and subjected to a hydrothermal reaction. After the reaction is completed, the mixture is filtered, washed, and dried to obtain a Pt / C catalyst.
[0013] Furthermore, the mass concentration of the urea solution in step (1) is 1% to 15%, and the mass ratio of the urea solution to the carbon carrier is 1 to 10:1.
[0014] Furthermore, the mass concentration of the carrier ethylene glycol mixed solution in step (2) is 3% to 15%.
[0015] Furthermore, the platinum salt precursor used in step (2) is chloroplatinic acid hexahydrate, platinum acetylacetonate or platinum acetate, and the mass concentration of the platinum salt precursor aqueous solution is 0.05% to 30%.
[0016] Furthermore, in step (2), the temperature of the hydrothermal reaction is 80 to 180° C., and the time is 2 to 72 hours.
[0017] The novel carrier treatment technology adopted in the present application and the high-performance Pt / C catalyst obtained by the above technology are as follows: urea is impregnated onto the carbon carrier by an equal amount impregnation method, and then mixed with a mixed solution of a platinum salt precursor, water and ethylene glycol after drying and grinding, and a high-performance Pt / C catalyst is prepared after hydrothermal treatment.
[0018] The present invention uses urea to treat the carrier, and the number of micropores of the treated carrier is significantly reduced, and the surface N content is significantly increased. Using this as a carrier, a high-performance Pt / C catalyst is prepared after hydrothermal treatment. The particle size distribution of the Pt nanoparticles of the Pt / C catalyst prepared in this way is between 1-10nm, and its electrochemically active specific surface area is 50 m 2 / g, and the half-wave potential is 0.87V. At the same time, the catalyst has good stability. After 50,000 cycles, the electrochemical active specific surface area only decreases by 2%, and the half-wave potential remains almost unchanged.
[0019] The catalyst prepared by the present invention also has good performance in membrane electrode measurement. Under normal pressure, its peak power density can reach 1.3W / cm 2 The catalyst is easy to prepare, has excellent performance, and has good prospects for industrial application. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is the particle size distribution diagram of Pt nanoparticles in Example 1.
[0021] Figure 2 It is the CV diagram of the catalyst prepared in Example 1 and commercial Pt / C.
[0022] Figure 3 is the LSV diagram of the catalyst prepared in Example 1 and commercial Pt / C.
[0023] Figure 4 This is a CV stability test chart of the catalyst prepared in Example 1.
[0024] Figure 5 This is the LSV stability test chart of the catalyst prepared in Example 1.
[0025] Figure 6 This is a membrane electrode performance test diagram of the catalyst prepared in Example 1. DETAILED DESCRIPTION
[0026] In order to enable those skilled in the art to better understand the solution of the present application, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present application.
[0027] It should be noted that the terms "including" and "having" and any variations thereof in the specification and claims of the present application and the above-mentioned drawings are intended to cover non-exclusive inclusions. For example, a process, method, system, product or apparatus comprising a series of steps or units is not necessarily limited to those steps or units clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or apparatuses. Example
[0028] Pretreatment process of carbon carrier: (1) Weigh 1 g of XC-72C carrier and place it in a beaker; (2) Weigh 0.8 g of urea and dissolve it in 4 g of deionized water; (3) Use a dropper to add the above urea aqueous solution to the weighed XC-72 C in four times, stirring evenly after each addition; (4) Dry the mixture in an oven at 80 degrees for 24 hours for later use; (5) Grind the dried sample.
[0029] Preparation of 20% Pt / C catalyst: (1) Weigh 0.8 g of the pretreated carbon support and place it in a 100 ml hydrothermal kettle; (2) Add 70 ml of ethylene glycol solution and sonicate for 30 minutes; (3) Add 0.53 g of chloroplatinic acid hexahydrate and stir evenly; (4) Hydrothermal at 120°C for 12 h; (5) After the hydrothermal reaction is completed, the 20% Pt / C catalyst is obtained after filtration, washing and drying.
[0030] Table 1 is the comparison of the specific surface area and pore size distribution of the carrier before and after urea treatment. Table 2 is the element analysis data of the carrier before and after urea treatment.
[0031] From Table 1, we can see that the surface micropore volume of XC-72C obtained after urea treatment is from 0.05cm 3 / g down to 0.03cm 3 / g, micropore specific surface area from 91m 2 / g down to 65m 2 / g, the average pore size increased from 4.7nm to 5.7nm. From Table 2, we can see that the surface nitrogen content increased from 0.5% to 2.2%, and the oxygen content increased from 2.0% to 8.7%. Furthermore, we can prepare a high-performance catalyst by using the catalyst obtained after urea treatment as a carrier.
[0032] Figure 1 This is the TEM image of the catalyst we prepared. From the image we can see that the particle size distribution of Pt nanoparticles of the Pt / C catalyst prepared using a urea-treated carrier is uniform, generally between 2-3nm.
[0033] Figure 2 The CV electrochemical test diagram of the catalyst prepared for us. From the figure, we can see that the electrochemically active specific surface area of the Pt / C catalyst prepared using the urea-treated carrier is larger than that of the Pt / C catalyst not treated with urea and the Pt / C catalyst of the commercial Johnson Matthey. Figure 3 The LSV electrochemical test diagram of the catalyst prepared for us. From the figure, we can see that the half-wave potential of the Pt / C catalyst prepared using the urea-treated carrier is 0.87V, which is significantly higher than the Pt / C catalyst not treated with urea and the Pt / C catalyst of the commercial Johnson Matthey Figure 4 , 5 This is the stability test result of the catalyst prepared by us. As can be seen from the figure, after 50,000 cycles, its electrochemical active specific surface area and half-wave potential did not show a significant decrease, indicating that this catalyst has good stability.
[0034] Figure 6 The test results of the membrane electrode prepared by us. From the figure, we can see that the power density of the membrane electrode prepared by the Pt / C catalyst prepared by the urea-treated carrier can reach 1.3W / cm 2 , higher than commercial Pt / C catalyst.
[0035] Table 1 sample <![CDATA[Specific surface area (m 2 / g)]]> <![CDATA[Micropore area (m 2 / g)]]> <![CDATA[Micropore volume (cm 3 / g)]]> XC-72 Before treatment 200 91 0.05 XC-72 after treatment 170 65 0.03 Table 2 sample C content N content O content XC-72 Before treatment 97.5% 0.5% 2.0% XC-72 after treatment 89.1% 2.2% 8.7% Example
[0036] Pretreatment process of carbon carrier: (1) Weigh 1 g of XC-72C carrier and place it in a beaker; (2) Weigh 0.4 g of urea and dissolve it in 4 g of deionized water; (3) Use a dropper to add the above urea aqueous solution to the weighed XC-72 C in four times, stirring evenly after each addition; (4) Dry the mixture in an oven at 80 degrees for 24 hours for later use; (5) Grind the dried sample.
[0037] Preparation of 20% Pt / C catalyst: (1) Weigh 0.8 g of the pretreated carbon support and place it in a 100 ml hydrothermal kettle; (2) Add 70 ml of ethylene glycol solution and sonicate for 30 minutes; (3) Add 0.53 g of chloroplatinic acid hexahydrate and stir evenly; (4) Hydrothermal at 120°C for 12 h; (5) After the hydrothermal reaction is completed, the 20% Pt / C catalyst is obtained after filtration, washing and drying. Example
[0038] Pretreatment process of carbon carrier: (1) Weigh 1 g of XC-72C carrier and place it in a beaker; (2) Weigh 1.2 g of urea and dissolve it in 4 g of deionized water; (3) Use a dropper to add the above urea aqueous solution to the weighed XC-72 C in four times, stirring evenly after each addition; (4) Dry the mixture in an oven at 80 degrees for 24 hours for later use; (5) Grind the dried sample.
[0039] Preparation of 20% Pt / C catalyst: (1) Weigh 0.8 g of the pretreated carbon support and place it in a 100 ml hydrothermal kettle; (2) Add 70 ml of ethylene glycol solution and sonicate for 30 minutes; (3) Add 0.53 g of chloroplatinic acid hexahydrate and stir evenly; (4) Hydrothermal at 120°C for 12 h; (5) After the hydrothermal reaction is completed, the 20% Pt / C catalyst is obtained after filtration, washing and drying. Example
[0040] Pretreatment process of carbon carrier: (1) Weigh 1 g of XC-72C carrier and place it in a beaker; (2) Weigh 0.8 g of urea and dissolve it in 4 g of deionized water; (3) Use a dropper to add the above urea aqueous solution to the weighed XC-72 C in four times, stirring evenly after each addition; (4) Dry the mixture in an oven at 80 degrees for 24 hours for later use; (5) Grind the dried sample.
[0041] Preparation of 20% Pt / C catalyst: (1) Weigh 0.8 g of the pretreated carbon support and place it in a 100 ml hydrothermal kettle; (2) Add 70 ml of ethylene glycol solution and sonicate for 30 minutes; (3) Add 0.53 g of chloroplatinic acid hexahydrate and stir evenly; (4) Hydrothermal at 150°C for 12 h; (5) After the hydrothermal reaction is completed, the 20% Pt / C catalyst is obtained after filtration, washing and drying. Example
[0042] Pretreatment process of carbon carrier: (1) Weigh 1 g of XC-72C carrier and place it in a beaker; (2) Weigh 0.8 g of urea and dissolve it in 4 g of deionized water; (3) Use a dropper to add the above urea aqueous solution to the weighed XC-72 C in four times, stirring evenly after each addition; (4) Dry the mixture in an oven at 80 degrees for 24 hours for later use; (5) Grind the dried sample.
[0043] Preparation of 20% Pt / C catalyst: (1) Weigh 0.8 g of the pretreated carbon support and place it in a 100 ml hydrothermal kettle; (2) Add 70 ml of ethylene glycol solution and sonicate for 30 minutes; (3) Add 0.53 g of chloroplatinic acid hexahydrate and stir evenly; (4) Hydrothermal at 180°C for 12 h; (5) After the hydrothermal reaction is completed, the 20% Pt / C catalyst is obtained after filtration, washing and drying. Example
[0044] Pretreatment process of carbon carrier: (1) Weigh 1 g of XC-72C carrier and place it in a beaker; (2) Weigh 0.8 g of urea and dissolve it in 4 g of deionized water; (3) Use a dropper to add the above urea aqueous solution to the weighed XC-72 C in four times, stirring evenly after each addition; (4) Dry the mixture in an oven at 80 degrees for 24 hours for later use; (5) Grind the dried sample.
[0045] Preparation of 20% Pt / C catalyst: (1) Weigh 0.8 g of the pretreated carbon support and place it in a 100 ml hydrothermal kettle; (2) Add 60 ml of ethylene glycol solution and ultrasonicate for 30 minutes; (3) Add 0.53 g of chloroplatinic acid hexahydrate and stir evenly; (4) Hydrothermal at 150°C for 12 h; (5) After the hydrothermal reaction is completed, the 20% Pt / C catalyst is obtained after filtration, washing and drying.
[0046] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A high performance Pt / C catalyst, characterized in that include: A carbon carrier and Pt nanoparticles loaded on the carbon carrier. The carbon carrier is treated with urea by an equal amount impregnation method before loading.
2. The high performance Pt / C catalyst according to claim 1, characterized in that: The particle size of the Pt nanoparticles is 1-10 nm, and the Pt loading is 10%-60% by mass.
3. The high performance Pt / C catalyst according to claim 1, characterized in that: After the carbon carrier is treated by an equal amount impregnation method, the surface micropore volume of the carbon carrier is 0.01-0.05 cm 3 / g, micropore specific surface area is 10~65m 2 / g, and the average pore size is 4~8nm.
4. The high performance Pt / C catalyst according to claim 1, characterized in that: After the carbon carrier is treated by the equal amount impregnation method, the surface nitrogen content is 0.5% to 5%, and the oxygen content is 5% to 15%.
5. The high performance Pt / C catalyst according to claim 1, characterized in that: The carbon carrier is XC-72C, Ketjen black, EC300J, Denka black carbon black or Black Pears 2000 carbon black.
6. A method for preparing a high performance Pt / C catalyst according to any one of claims 1 to 5, It is characterized by the following steps: (1) Pretreatment of the carbon carrier: urea is dispersed in water to form a urea solution, and then the solution is mixed evenly with the carbon carrier, and left at room temperature for 12 to 120 hours, and then placed in an oven at 60 to 120°C for 24 to 48 hours, dried and ground to obtain a pretreated carbon carrier; (2) Preparation of supported catalyst by reduction: The carbon support pretreated in step (1) is added to an ethylene glycol solution to form a support ethylene glycol mixed solution, and an aqueous solution of a platinum salt precursor is added to set the Pt loading to 10 wt% to 60 wt%. The mixture is sealed and subjected to a hydrothermal reaction. After the reaction is completed, the mixture is filtered, washed, and dried to obtain a Pt / C catalyst.
7. The preparation method according to claim 6, characterized in that: The mass concentration of the urea solution in step (1) is 1% to 15%, and the mass ratio of the urea solution to the carbon carrier is 1 to 10:
1.
8. The preparation method according to claim 6, characterized in that: The mass concentration of the carrier ethylene glycol mixed solution in step (2) is 3% to 15%.
9. The preparation method according to claim 6, characterized in that: The platinum salt precursor used in step (2) is chloroplatinic acid hexahydrate, platinum acetylacetonate or platinum acetate, and the mass concentration of the platinum salt precursor aqueous solution is 0.05% to 30%.
10. The preparation method according to claim 6, characterized in that: The temperature of the hydrothermal reaction in step (2) is 80 to 180° C. and the time is 2 to 72 hours.
Citation Information
Patent Citations
Preparation method of nitrogen-doped carbon-loaded platinum-based catalyst for fuel cell
CN109585857A
Pt / C catalyst and preparation method and application thereof
CN114171749A
Nitrogen-doped porous carbon-supported Pt fuel cell cathode catalyst as well as preparation method and application thereof
CN118763239A
Novel Synthesis method of Pt / C catalyst, catalyst and PEMFC using the same
KR1020110015774A